Investigation of short-term creep deformation mechanisms in MarBN steel at elevated temperatures - Benaarbia, Adil; Xu, Xu; Sun, Wei; Becker, Adib; Jepson, Mark (Elsevier, 2018)
This paper reports the short-term creep behavior at elevated temperatures of a MarBN steel variant. Creep tests were performed at 3 different temperatures (625oC, 650oC and 675oC) with applied stresses ranging from 160 MPa to 300 MPa, and failure times from 1 to 350 hours. Analysis of the macroscopic creep data indicates that the steady-state creep exhibits a power-law stress dependence with an exponent of 7 and an activation energy of 307 kJ.mol-1, suggesting that dislocation climb is the dominant rate-controlling creep mechanism for MarBN steel. Macroscopic plastic instability has also been observed, highlighted by an obvious necking at the rupture region. All the macroscopic predictions have been combined with microstructural data, inferred from an examination of creep ruptured samples, to build up relations between macroscopic features (necking, damage, etc.) and underlying microstructural mechanisms. Analysis of the rupture surfaces has revealed a ductile fracture mode. Electron Backscatter Diffraction (EBSD) analysis near to the rupture surface has indicated significant distortion and refinement of the original martensitic substructure, which is evidence of long-range plastic flow. Dislocation pile-ups and tangles from TEM were also observed near substructure boundaries and precipitate particles. All of these microstructural observations suggest that creep is influenced by a complex interaction between several elements of the microstructure, such as dislocations, precipitates and structure boundaries. The calculated stress exponent and activation energy have been found to agree quantitatively with the highlighted microstructural features, bearing some relationships to the true observed creep microstructures.